The Effectiveness of Radiofrequency Ablation of Medial Branch Nerves for Chronic Lumbar Facet Joint Syndrome in Patients Selected by Guideline-Concordant Dual Comparative Medial Branch Blocks. Issue 5 (14th October 2019) - Conger, Aaron; Burnham, Taylor; Salazar, Fabio; Tate, Quinn; Golish, Mathew; Petersen, Russell; Cunningham, Shellie; Teramoto, Masaru; Kendall, Richard; McCormick, Zachary L
Abstract: Objectives: Although the effectiveness of lumbar medial branch radiofrequency ablation (RFA) for the treatment of zygapophyseal joint (z-joint)–mediated low back pain has been characterized, few studies have described outcomes in patients selected using a guideline-concordant paradigm of ≥80% pain relief with dual comparative medial branch blocks (MBBs). We investigated long-term treatment outcomes of patients selected according to this paradigm. Design: Cross-sectional cohort study. Methods: The medical records of 111 consecutive patients were reviewed; 85 met inclusion criteria. A standardized telephone survey was used to capture current numerical rating scale (NRS) and Patient Global Impression of Change (PGIC) scores. The primary outcome was the proportion of patients reporting ≥50% reduction of index pain. Binary logistic regression analysis was performed to explore associations between the primary outcome and covariates, including age, duration of pain, presence of scoliosis, degenerative spondylolisthesis, and >75% disc height loss. Results: At six to 12, 12–24, and >24 months, 63.2% (95% confidence interval [CI] = 41–85%), 65.6% (95% CI = 49–82%), and 44.1% (95% CI = 27–61%) of patients reported a ≥50% pain reduction ( P  =   0.170), respectively. At a minimum of six months, 70.6% of patients reported a pain reduction of two or more points (minimally clinically important change), and 54.1% reported a PGIC score consistent with "much improved" or better. Older age and a smaller Cobb angle were associated with a ≥50% pain reduction ( P  <   0.05). Conclusion: Lumbar medial branch RFA is an effective, durable treatment for a significant proportion of patients with recalcitrant lumbar z-joint pain when candidacy is determined by the guideline-concordant paradigm of ≥80% pain relief with dual comparative MBBs.